Management and business of autonomous vehicles: a systematic integrative bibliographic review. (2019) - Cavazza, Bruna Habib; Gandia, Rodrigo Marçal; Antonialli, Fabio; Zambalde, André Luiz; Nicolaï, Isabelle; Sugano, Joel Yutaka; Neto, Arthur De Miranda
This paper reviews the management and business research field of autonomous vehicles (AVs) in a bibliometric context aiming to identify strategies, practices, and management tools; and summarises the existing studies and highlight research gaps. Methodologically, the study is qualitative and descriptive, based on a bibliometric review on Web of Science, Scopus, and Science Direct, followed by a systematic integrative review. Results show that, in the near future, AVs will certainly be introduced in the society. However, such insertion is still surrounded by uncertainties, doubled by governments' lack of planning. The absence of business-related studies can be a determinant for AVs introduction, once business models (BM) play an important for AVs advancement. Nevertheless, especially in Europe, studies related to AVs 'car-sharing' seem to be predominant. As such, we observe a research gap regarding BM and platforms and radical and responsible innovation theories.